PERAN GURU DI WILAYAH PESISIR DAN TERPENCIL - Waqif, Abdul (Pascasarjana Universitas Negeri Makassar, 2017)
Poverty of the people in the coastal and remote islands can occur due to complex causes, among others because of: (1) a wrong paradigm or view of life that is marked by fatalism and living surrender to the conditions of his life; (2) low experience and level of education; (3) limited ownership of assets; (4) rely solely on individual efforts in living their lives; (5) dependence on retainer snares; (6) isolation due to limited facilities, infrastructure, mobility and information; and helplessness. The impact of poverty on education causes high rates of dropout. A person can become poor because of the low level of education, and vice versa, someone chooses to drop out of school because of the lack of economic level he has. Teachers have a very strategic role in helping to overcome poverty, especially in coastal and remote islands, in addition to carrying out the task of educating and teaching in schools, the teacher also acts as a servant in the community, namely as a problem solver, facilitator, innovator, and partner friend.